TO THE PROBLEM OF RADIATION-INDUCED CARCINOGENESIS AFTER TREATMENT OF HODGKIN’S LYMPHOMA AND ACUTE LYMPHOBLASTIC LEUKEMIA IN CHILDREN AND ADOLESCENTS - O. I. Scherbenko; R. A. Parkhomenko (Сибирский онкологический журнал)
Twenty-six cases with secondary malignant tumors in children and adolescents receiving treatment for Hodgkin’s lymphoma and acute lymphoblastic leukemia were analyzed. In all cases the lesion had developed in an area of previous radiation treatment. The interval between the primary treatment and secondary cancer development was from 3 to 29 years. The radiation therapy dose was from 12 to 45 Gy. Treatment of secondary cancer was successful only in 5 patients, the remaining patients died of disease progression. The risk of developing secondary cancer should be considered when planning treatment for patients with hemoblastosis. In cases with favorable prognosis (complete remission after induction chemotherapy and other signs of favorable prognosis) it is advisable to withhold radiation therapy as the most important risk factor for cancer.